Hierarchical distance and employees' commitment as conditioning of team-based work in the Spanish public sector - Triguero-Sánchez, Rafael (2021)
Team-based work (TBW) plays a crucial role in the success and quality of public services. In the context of the Spanish public sector, our study evaluates if a low level of hierarchical distance (HD) in public organizations condition the public employees’ commitment (EC) as well as TBW, assessed in terms of participation and consensus among team members. Simultaneously, we evaluated to what extent EC help to enhance TBW. Employing a sample of 213 government organizations from the south of Spain through a model of structural equations, we were able to answer the above questions. Our results revealed that team-based work functions more successfully within public organizations where there exists little verticality in their structures, norms, values and rules – in simplest terms, where there is minimal organizational HD. Such results also suggest that although regulations exist in the Spanish public sector, should public organizations attempt to be less vertical and more horizontal, they would perhaps have public servants that were more committed to their organizations. As a result, servants view the organization as their own and remain loyal. Finally, from an academic perspective, this study could be one of few to research and evaluate the hierarchical role and employees’ commitment to the functioning of public employees based on participation and consensus in their work teams.